1997
DOI: 10.1002/(sici)1098-2744(199701)18:1<19::aid-mc3>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

ASPB10 insulin induction of increased mitogenic responses and phenotypic changes in human breast epithelial cells: Evidence for enhanced interactions with the insulin-like growth factor-I receptor

Abstract: The human insulin analogue ASPB10 has been reported to have increased affinity for the insulin receptor and to cause breast cancer in female rats. In the study reported here, we investigated whether ASPB10 has an increased mitogenic potency and induces a transformed phenotype in cultured human breast cells. In both MCF-10 cells (a non-malignant human breast line) and MCF-7 cells (a human breast cancer cell line), ASPB10 was approximately twofold more potent than insulin in competing for 125I-insulin binding bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 19 publications
3
70
1
1
Order By: Relevance
“…In the majority of studies the binding affinity of insulin X10 to IR has been found to be increased 200-400% relative to that of human insulin. It was also noted by these early studies that the binding affinity of insulin X10 to IGF-1R was increased compared with that of human insulin [17,18] but with a fairly low affinity compared with IGF-1 itself, an effect that has subsequently been confirmed by a number of authors [19][20][21][22]. In addition to the increased receptor affinities, [12] insulin X10 was shown to have an increased in vitro ability to stimulate cell growth and DNA synthesis, and Bornfeldt and colleagues speculated that this was due to a substitution in the insulin X10 molecule that made this analogue more chemically similar to the IGF-1 molecule [18].…”
Section: Understanding Insulin X10mentioning
confidence: 77%
See 2 more Smart Citations
“…In the majority of studies the binding affinity of insulin X10 to IR has been found to be increased 200-400% relative to that of human insulin. It was also noted by these early studies that the binding affinity of insulin X10 to IGF-1R was increased compared with that of human insulin [17,18] but with a fairly low affinity compared with IGF-1 itself, an effect that has subsequently been confirmed by a number of authors [19][20][21][22]. In addition to the increased receptor affinities, [12] insulin X10 was shown to have an increased in vitro ability to stimulate cell growth and DNA synthesis, and Bornfeldt and colleagues speculated that this was due to a substitution in the insulin X10 molecule that made this analogue more chemically similar to the IGF-1 molecule [18].…”
Section: Understanding Insulin X10mentioning
confidence: 77%
“…The binding of insulin X10 to hybrid receptors is unknown at present, but is currently under investigation. Some studies have found an increase in the maximal attainable response after stimulation with insulin X10 [18,21], whereas this has not been found by others [11,19,38]. However, it remains a possibility that in some cell types and for some responses, insulin X10 may be able to induce a higher response than human insulin.…”
Section: Understanding Insulin X10mentioning
confidence: 91%
See 1 more Smart Citation
“…5a). Quantification of five different experi- [10,14]. In contrast, the insulin analogue HMR1423 behaved like regular insulin, while HMR1964 was even less effective in stimulation of [ 3 H]thymidine incorporation (Fig.…”
Section: Dephosphorylation Kinetics Of the Insulin Receptormentioning
confidence: 99%
“…In this insulin analogue the histidine in position 10 of the B chain of the insulin molecule is replaced by aspartic acid [4]. The mutation of this insulin analogue has been shown to induce mitogenic effects [5][6][7], and according to the authors' [1] conclusion, could also be responsible for the observed liver transdifferentiation. Using the furin-cleavable insulin for the lentiviral transductions we detected a decrease in blood glucose concentration of STZ-diabetic rats from 22.3±3.4 to 15.6±2.1 mmol/l after 3 days and to 15.0±2.8 mmol/l after 30 days.…”
Section: Stz Streptozotocinmentioning
confidence: 99%